A new correlation for carbon dioxide boiling heat transfer coefficient outside evaporating tubes. (10th December 2020) - Liu, Shengchun; Qi, Haifeng; Nian, Victor; Liu, Bin; Dai, Baomin; Sun, Zhili; Li, Xueqiang; Yuan, Jun
Abstract: The Kigali Amendment to the Montreal Protocol encourages replacing hydrofluorocarbons or HFCs with natural refrigerants such as carbon dioxide. Since current CO2 transcritical systems have lower efficiency as compared to HFC systems, this study is proposed to carry out theoretical and experimental investigations of CO2 pool boiling heat transfer performance for efficiency improvements. The theoretical and experimental investigations are carried out for a smooth and three mechanically enhanced tubes under heat flux values ranging from 10 to 50 kW m −2 and evaporating pressures ranging from 2 to 4 MPa. The special structures of enhanced tube surface are favorable for the formation and maintenance of vaporization cores and for expelling the gas bubbles in the evaporation tubes. Results from the experimental investigations suggest that the heat transfer coefficient can be improved by a factor of 1.50–1.70, 1.58–1.82, and 1.94–2.23 respectively when using the three mechanically enhanced as compared to using the smooth tube. Such improvements in heat transfer coefficient can translate to an energy efficiency improvement of approximately 15.2%, 18.6% and 24.8% respectively. Based on the experimental data, a robust and simplified model for computing heat transfer coefficient is further proposed as a correlation of evaporating pressure and heat flux. The maximum deviation of the calculated and tested heat transfer coefficient is within ±8.73% for smooth tube and within ±15% for mechanically enhanced tubes. Findings from this study can provide a fundamental basis for improving the heat transfer performance of CO2 systems from the perspective of engineering design.